On the issue of automatic form accuracy during processing on CNC machines; Revista Facultad de Ingenieria; No. 103 - Ovsyannikov V. E. Viktor Evgenjevich; Nekrasov R. Yu. Roman Yurjevich; Putilova U. S. Uljyana Sergeevna; Ilyashchenko D. P. Dmitry Pavlovich; Verkhoturova E. V. Elena Vladimirovna (2022, 2022)
Title screen